Antipyretic and antitumor effects of a purified polysaccharide from aerial parts of Tetrastigma hemsleyanum. (10th May 2020) - Zhu, Bingqi; Qian, Chaodong; Zhou, Fangmei; Guo, Jingjing; Chen, Nipi; Gao, Chengxian; Jin, Bo; Ding, Zhishan
Abstract: Ethnopharmacological relevance: Tetrastigma hemsleyanum Diels et Gilg (Sanyeqing) is traditionally used as a folk medicine for the treatments of inflammation, high fever, hepatitis and cancer, and can improve the immune function of the patient. It belongs to the family of Vitaceae, and is mainly distributed in southeast China (Yunnan province) and can be found in India (Andaman Islands), Myanmar, Thailand, Vietnam, Malaysia and Indonesia in the valleys with 1100–1300 m above the sea level. Aim of the study: The present study aimed to characterize the chemical properties of a purified polysaccharide extracted from the aerial part of Tetrastigma hemsleyanum (SYQP) and investigate its antipyretic and antitumor effects in mice models. Materials and methods: Water-soluble crude polysaccharides from the aerial parts of Tetrastigma hemsleyanum were extracted and fractionated by DEAE and gel permeation chromatography. Homogeneity, molecular weight, monosaccharide composition, and FTIR analysis were performed to characterize the SYQP. Antipyretic effect of SYQP was examined using Brewer's yeast induced hyperthermia test. Antitumor effect was investigated using H22 tumor bearing mice. The serum cytokines were determined to evaluated the biological activities of SYQP. Results: SYQP was composed of galacturonic acid (GalA), glucose (Glc), mannose (Man), arabinose (Ara), galactose (Gal), and rhamnose (Rha) with a molar ratio of 11.3:7.1:2.5:1.0:0.9:0.5 and it had an average molecular weight of 66.2 kDa. The oral administration of SYQP at 200 and 400 mg/kg could markedly suppress the hyperthermia of mice induced by Brewer's yeast and decrease the production of cytokines especially prostaglandin E2 (PGE2) in the serum of mice. SYQP inhibited the growth of H22 tumor in mice with inhibitory rate of 39.9% at the administration dose of 200 mg/kg and increased the production of cytokines such as tumor necrosis factor-alpha (TNF-a) and interferon γ (IFN-γ). Experimental results showed that the preventive administration of SYQP before lipopolysaccharide (LPS) reduced the high cytokine levels such as IL-6, IL-10 and IFN-γ, indicating that SYQP might act as a competitor with LPS to interact with toll like receptor 4 (TLR4), which further regulated the secretion of cytokines. Conclusion: The anti-inflammatory and antitumor activities of SYQP might be related to its regulation of host immune function by controlling the secretion of cytokines. Graphical abstract: Image 1 Highlights: The polysaccharide of aerial parts of Sanyeqing (SYQP) was extracted and purified. Antipyretic and antitumor effects of SYQP related to the serum cytokines regulation. SYQP may interact with TLR4 to regulate the secretion of cytokines.